New Entrepreneurship Paradigm in the Era of Disruption - Rio Wijaya (Enigma Institute, 2023)
This emerging paradigm presents unparalleled difficulties and prospects for entrepreneurs. With the growing interconnectedness and reliance on technology in society, entrepreneurs need to employ inventive and flexible cognitive processes. They must be ready to confront unforeseen market fluctuations, escalating competition, and evolving customer demands. Profound innovation and the implementation of technology are the essential factors for attaining success in this period of upheaval. The contemporary model of entrepreneurship in the age of disruption highlights the significance of novelty, adaptability, durability, societal influence, and customer-centricity. In the age of disruption, entrepreneurs must possess a relentless thirst for knowledge, be prepared to swiftly adjust to new circumstances, and possess the courage to embrace risks. In addition, it is imperative for them to utilize technology and engage in collaborative efforts with external stakeholders in order to establish a robust innovation ecosystem. In the face of increased risks and heightened uncertainty, entrepreneurs have the capacity to attain bigger earnings by exercising prudent risk-taking and capitalizing on emerging possibilities. This emerging paradigm embodies shifts in corporate practices, emphasizing sustainability, the creation of additional value, and the promotion of positive societal and environmental outcomes. Entrepreneurs who thrive in the age of disruption are those who can effectively integrate innovation, flexibility, and customer-centricity, all while operating their businesses with a heightened sense of social responsibility.